2016
DOI: 10.1038/srep37451
|View full text |Cite
|
Sign up to set email alerts
|

Interleukins 17 and 23 in patients with gastric neoplasms

Abstract: Recently there has been heightened interest in the potential significance of interleukin (IL)-17 and IL-23 in the development/progression of human malignancies. Here, we analyzed the systemic levels of these cytokines in 75 patients with different types of gastric neoplasms (carcinoma, gastrointestinal stromal tumors, neuroendocrine neoplasms, and lymphomas) and 42 healthy volunteers. We found that patients with all types of gastric neoplasms have significantly lower IL-23 levels. However, in comparison to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 46 publications
2
15
1
Order By: Relevance
“…In the progression of gastric carcinogenesis, initially, H. pylori strongly induces specific cytokines, but the immune response generally is not sufficient to clear the H. pylori infection completely from the human epithelial cells. As a result, chronic inflammation may occur[ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the progression of gastric carcinogenesis, initially, H. pylori strongly induces specific cytokines, but the immune response generally is not sufficient to clear the H. pylori infection completely from the human epithelial cells. As a result, chronic inflammation may occur[ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other types of cytokines, such as the interleukin (IL) family (e.g., IL-17 and IL-6), contribute to the inflammatory response 30 , 31 . Indeed, many studies have reported abnormal IL concentrations in GC patients and suggested promising indicators of GC development 32 , 33 . Therefore, further studies are needed to identify whether genetic polymorphisms associated with other cytokines can modify the diet effect that increases the risk of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that the interaction of cytokines showed an important role in the development and progression of malignant tumors. Previous studies have revealed that IL-17 was involved in tumor occurrence, metastasis, angiogenesis, immune-resistance and other processes [26][27][28], and confirmed that IL-17 signaling pathway also played an important role in the occurrence and progression of GC [29], breast cancer [30] and pancreatic cancer [31]. Meanwhile, Liu et al [32] obtained the data of Helicobacter pylori GC samples from TCGA and revealed that cytokine-cytokine receptor interaction was enriched in H. pylori (+) GC through GO and KEGG analysis.…”
Section: Discussionmentioning
confidence: 99%